The enolases of ice plant and Arabidopsis contain a potential disulphide and are redox sensitive - Anderson, Louise E.; Alex Dong Li; Stevens, Fred J. (Phytochemistry (Oxford), 1998)
The simulated structures of the enolases of Arabidopsis and the common ice plant contain a pair of Cys residues in the correct orientation to form a disulphide bond. Formation of this disulphide might be expected to affect the positioning of several residues in the active site. The enzyme in crude extracts of these two plants is activated by oxidation. Apparently formation of the disulphide crosslink enhances catalysis. The enolases from tomato leaves, maize roots and castor bean embryos lack one of these Cys residues and are not redox sensitive. It seems possible that enolase is redox-regulated by a cytosolic thioredoxin system in a limited number of plant species including ice plant and Arabidopsis. The enolases of Arabidopsis and ice plant contain cysteine residues in a region where, if oxidized they might be expected to affect the positioning of the residues in the active site. The enzyme in crude extracts is oxidatively activated and may therefore be subject to redox regulation in vivo.